Governmental factors for household energy savings: Adding the theory of planned behavior - Abduh, Muhammad Abduh (Jurnal Ilmiah Administrasi Publik, 2017)
Household is examined a fundamental lifestyle discipline, for several dialectics. Various  fundamental human interests are fulfilled by household, from protection and assurance to social affiliations and identification. Household should be comfortable. Appropriate conditions can be started with energy efficiency.  That is, the energy savings can be started from the household.  According to Statistics Indonesia (2013), household energy savings (HES) was done only 36,85%.  This study set out to investigate the relationship between house energy savings behaviors with governmental factors by implementing the theory of planned behavior (TPB). This is a cross-sectional study operates a unique dataset compiled by Statistics Indonesia:  Village Potential Statistics (VPS) Year 2011 and Environmental Care Behavior Survey (ECBS) Year 2013. Variables connected to HES were decidedby applying amultivariable logistic regression model running manual backward stepwise regression.  All of model, all variables of the planned behavior theory and its addition were significantly correlated with HES besides Intention (Very sincere: OR = 1.08, 95% CI: 0.99, 1.16). The results of this study show/indicate that intention, attitude, subjective norm and perceived behavioral control as an explanation of household energy savings after examine the extension of five government-based variables.